URGENCY, LEGAL FORM AND ENFORCEMENT, SYSTEMATIC PRINCIPLES OF COUNTRY - Idham (Faculty of Law-Universitas Bandar Lampung, 2021)
Outlines of State Policy (GBHN) are one of the central issues that are currently being discussed in the state administration. In various occasions of socialization of the four pillars of the state by the People's Consultative Assembly (MPR), the discourse on reviving the GBHN as a guideline for national development planning became one of the materials. This is inseparable from Recommendation No. 2 of MPR RI Decree No. 4/MPR/2014 concerning Recommendation of MPR RI for 2009-2014 term of office. The results of a careful study in responding to polemics bring back the Outline of State Policy (GBHN) as recommended by the MPR RI for the 2014-2019 period which involves the participation of the people throughout Indonesia by involving various components as the direction of development that they feel. The substance in the Main Principles of State Policy only contains strategic policies that will become a reference for the preparation of development policies by the government.